Cultural Identity Negotiation in Digital Era: A Study on Millennial Entrepreneurs’ Perspective on Feng Shui in Modern Business Practices - Albert Albert; Rizka Tri Laksmi; Dhendy Hamdani (Cakrawala Repositori IMWI)
The continued use of Feng Shui among millennial entrepreneurs in Indonesia presents an intriguing contradiction, in which a generation widely characterized as rational, digital, and data-driven continues to incorporate traditional cultural practices into contemporary business practices. This research aims to explore how Indonesian millennial entrepreneurs interpret Feng Shui in business contexts and how it shapes their entrepreneurial identities. Based on a constructivist paradigm, this research employed a qualitative Interpretative Phenomenological Analysis (IPA) approach. Data were collected through in-depth interviews with eight millennial entrepreneurs, consisting of four Feng Shui believers and four non-believers. The findings indicate that Feng Shui beliefs are not monolithic but operate along a spectrum, ranging from deep structural dependence to pragmatic adoption. Believers integrate modern analytical approaches with ancestral wisdom rather than viewing them as mutually exclusive, while non-believers often maintain broader understandings of luck and Qi and demonstrate a high level of social tolerance toward such practices. Identity negotiation occurs through reactive communication strategies, in which believers do not actively promote their practices but are willing to share their perspectives when asked, thereby maintaining their professional image as modern, data-driven leaders. This research concludes that Indonesian millennial entrepreneurs do not perceive tradition and modernity as opposing dichotomies but rather as complementary resources that are flexibly integrated into their hybrid business identities.